Genetic Heterogeneity of Cebocephaly. Issue 1 (March 1974) - Holmes, Lewis B.; Driscoll, Shirley; Atkins, Leonard
Abstract : Three infants with cebocephaly with entirely different aetiologies are described: one possibly representing the effect of a single mutant gene, one with apparent E trisomy, and one with D trisomy. In comparison with other reported patients, it is likely that infants with cebocephaly and no associated chromosomal abnormality have few, if any, extracranial malformations.